An Attribute of a Female Stroke Patient of Bangladesh: Implementation ICF Model and Clinical Reasoning Skill (Global Journal of Medical Research, 2020)
Stroke is the disorder where the brain is damaged either by a blockage in the blood vessels or rupture of the blood vessels of the brain. It is the 5 th common cause of death and the leading cause for disability in most of the countries in the world. It is evident that a major group of the population dealing with a prolonged Disability-Adjusted life years where the clinician and rehabilitation practitioners are treating them with the traditional medical model. As a result, the treatments are often devised according to physical parameters and the outcome remains incomplete and unsatisfactory. Therefore the introduction of the bio-psychosocial model is crucial. This case study focused on a female post stroke patient's successful recovery in functional ability following a rehabilitation protocol which was provided by a bio-psychosocial approach. This study also emphasized how the clinician's expertise, proper Intervention time allocation, appropriate clinical reasoning skill, patient's willingness, and family support acted as the contributory factors for the success.
Keywords: stroke; ICF model; clinical reasoning